Correlation between Level of Personal Well-being and Spirituality - Danylchenko, Tetiana (Journal of Education Culture and Society, 2020)
Aim: The aim of this paper is to define the correlation between experiencing personal well-being and manifestations of spirituality of an individual. Methods: The study involved the citizens of Chernihiv (average age – 33.2 years old): 96 people in total, 40 men and 56 women. The following methods were used: a) to measure the components of personal well-being – Satisfaction with Life scale by E. Diener, Psychological well-being scale by С. Riff, Questionnaire of parameters of subjective social well-being by T. Danylchenko; b) to measure the spiritual component – EPU Plus (Egoism - Personal Uniqueness) by L. Z. Levit, Methodology of measuring social interaction (mentality aspect) by G. L. Voronin. Results: The source of experiencing personal well-being is positive health (physical abilities, absence of physical limitations). Factors that decrease personal well-being are low level of tolerance and the pursuit of pleasure. Personal well-being is ensured by belief about collaboration and experiencing positive health as a state of readiness for activity. Psychological well-being has a negative correlation with basic egoism (the pursuit of pleasure) and a positive one with social egoism (ability to comply one’s needs with the group interests, following social rules and norms). Subjective social well-being relates to the highest egoism (unique self-realization, realization of existing potential in an acceptable way). The orientation towards achieving personal or public goals determines the peculiarities of experiencing well-being in the eudaemonic and hedonistic dimensions.